The Understanding of Growth of Transport-Stop Node on Development Axis as Base of Development of New Strategy of Local Development1 - EKO SANTOSO; HERU PURBOYO; DEWI SAWITRI (Jurnal Studi Pemerintahan, 2013)
Development-Axes (DA) theory , is a theory which is originally stated by Pottier (1963), and restated by Hilhorst (1972) as wellas stated as an alternative growth theory (Paelinck and Nijkamp, 1975, 1978; Richardson 1978, 198, 2011) in explaining theexistence of nodes or centers along development axes and the end-point cities (Richardson, 1978,1981). or prime center or growthpole (Hilhorst, 1972) connected. Some of the real evidences of the implementation are the growing of many cities along highways inAmerica, along Grote Postweg road in Indonesia, and in many other countries. So it can be said that the theory is significance asdevelopment strategy in the world, especially in making place from transport-stop node which has role as infant settlement to belarger settlement (maybe as town or city in the future) along development axes. This paper focuses on seeking theoretical explanationas new understanding about how the growth of transport-stop node (as one of the local nodes) along DA that is influenced by theflow of people goods along the axis. We found that the growth cannot be explained by resource-based growth theory alone andneither other conventional theories of city growth. In fact, not all transport-stop node along DA could have same growth whether theflow of people and goods are equal along the DA. Based on the observation and in-depth interview as well as questionnaire, wefound that the growth of transport-stop node is initiated by the existence of transport facility or service at development axes. We alsofound that the growth of transport-stop node has five stages of growth and the “attractiveness” as the significant factor to the growthof transport-stop node to be lager settlement. We argue that the implication of the explanation to the policy is useful indecentralized era in Indonesia.